Relationship of urinary pH to symptoms of 'cystitis'. Issue 779 (September 1990) - Brumfitt, W.; Hamilton-Miller, J. M.; Cooper, J.; Raeburn, A.
Abstract : The pH of urine samples from patients suffering symptoms suggesting urinary infection (e.g. dysuria, frequency, urgency) was measured while the patients were symptomatic and again when they had become asymptomatic. There was no correlation between the urine pH and the incidence or number of symptoms. No differences were observed between either the distribution or means of urine pH values in symptomatic and asymptomatic patients. There were also no significant differences in either symptomatology or urine pH between patients with significant bacteriuria and those without significant bacteriuria. These results cast doubt upon the traditional (but unproved) belief that alkalinizing the urine helps to reduce symptoms of dysuria and/or frequency, whether or not associated with urinary infection.